A expansão urbana da região metropolitana de Belo Horizonte e suas implicações para a redistribuição espacial da população: o caso do município de Nova Lima - 1991-2000 - Renata Guimaraes Vieira de Souza (2005)
Belo Horizonte´s metropolitan area demographic growth is not in the Capital but in the surrounding area. This phenomenon can be called Space Inversion of Demographic Growth and the main cause is the change in the intra-metropolitan migration, which has been very important for the space redistribution of population. This population redistribution is related to the state market, which through the increase of prices segregate poor people to outskirts, characterized by the lack of structure. On the other hand, the lack of security, the violence of big cities and pollution, makes rich people move from the Capital as well.The main purpose of this thesis is to analyze the dynamic of the urban expansion to Nova Lima. Economics and Demographics characteristics of the intra-metropolitan emigrants that used to live in Belo Horizonte and moved to Nova Lima will be analyzed. Besides that, the daily journeys between Belo Horizonte and Nova Lima will also be studied to identify whom and why this kind of movement exists.